Scaling up innovations in smallholder agriculture: Lessons from the Canadian international food security research fund - Shilomboleni, Helena; Owaygen, Marwan; Plaen, Renaud de; Manchur, Wendy; Husak, Laura (Elsevier, 2019)
Scaling up food security innovations in low-income rural environments has often failed to achieve substantive and lasting results. This poor performance can be attributed to dominant, linear approaches associated with spreading innovations which entail technology research and development and subsequent transfer to farmers. Such approaches tend to overlook complexity elements and non-linear processes in smallholder agriculture, including multiple stress factors such as climate variability and economic risks that make the uptake of new agricultural innovations more unpredictable. This article presents programmatic lessons from the Canadian International Food Security Research Fund (CIFSRF) on scaling up. It considers projects that: i) deployed successfully pilot-tested innovations to reach and benefit large numbers of beneficiaries; and projects that ii) used innovations as an entry point to catalyse systematic change in the food and agricultural sector. The paper also outlines several key scaling up principles that can encourage better understanding of relevant socio-ecological dynamics and complexities in intervention areas as a way to support innovations (at scale) that can contribute to more sustainable system outcomes. Finally, the paper reflects on how predominant definitions of impact at scale, centered around rather narrow indicators around economic growth and technology transfer, might consider more holistic goals that encompass integrated agricultural interventions that advance sustainable agri-food system outcomes.